1993
DOI: 10.1038/bjc.1993.40
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis (the 1992 Frank Rose Memorial Lecture)

Abstract: Summary Apoptosis is a mode of cell death with characteristic structural features. These appear to result from a set of discrete cellular events that are regulated by gene expression. Oncogenesis and oncosuppressor genes are involved in this regulation. The role of c-myc is of particular interest, as it can act as a bivalent regulator, determining either cell proliferation or apoptosis, depending on whether free movement around the cell cycle is supported (by growth factors) or is limited by growth factor depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
215
1
7

Year Published

1996
1996
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(232 citation statements)
references
References 50 publications
9
215
1
7
Order By: Relevance
“…Model 2: Programmed cell death Here, prevention of programmed cell death (PCD) in tumour cells normally depends on paracrine growth factors secreted by adjacent cells (Kataoka et al, 1993;Wyllie, 1993;Harrington et al, 1994;Isaacs, 1994;Boudreau et al, 1996;Panayiotidis et al, 1996). The model assumes that the tumour has become too large for paracrine growth factors from normal tissue to have a significant effect.…”
Section: Methods and Results Model 1: Angiogenesismentioning
confidence: 99%
“…Model 2: Programmed cell death Here, prevention of programmed cell death (PCD) in tumour cells normally depends on paracrine growth factors secreted by adjacent cells (Kataoka et al, 1993;Wyllie, 1993;Harrington et al, 1994;Isaacs, 1994;Boudreau et al, 1996;Panayiotidis et al, 1996). The model assumes that the tumour has become too large for paracrine growth factors from normal tissue to have a significant effect.…”
Section: Methods and Results Model 1: Angiogenesismentioning
confidence: 99%
“…Strictly speaking, apoptosis is de®ned by morphological features. It is characterized by cell shrinkage, violent blebbing of the plasma membrane and chromatin condensation (Wyllie, 1993). Unlike a necrotic cell, the apoptotic cell does not leak internal contents and it does not induce an in¯ammatory response.…”
Section: C-myc Structure and Functionmentioning
confidence: 99%
“…In the early 1990s Cleveland and Evan and their colleagues established de®nitively that c-Myc can also activate apoptosis (Askew et al, 1991;Evan et al, 1992), a cell suicide program that is intrinsic to metazoan cells (Kerr et al, 1972;Wyllie, 1993). Toxic e ects of elevated c-Myc expression were noted anecdotally by many investigators in the 1980s and reported by several laboratories (e.g.…”
mentioning
confidence: 99%
“…Apoptosis is a characteristic type of cell death and plays an 2.4. Analysis of fragmented DNA important role in cell growth, differentiation and tissue develTo separate large DNA fragments, the cells were resuspended in 50 opment [6,7]. Although many biochemical changes, including lal of PBS (5 × 106 cells) after the and 50 gl of prewarmed low melting point agarose (1% in PBS) was added.…”
Section: Dna Fragmentationmentioning
confidence: 99%